Impact of country of origin effect on the automobile market in Singapore. - Chua, Yee Hao. (2008)
The study seeks to investigate the impact of Country of origin (COO) on the automobile market in Singapore. It empirically examines the COO phenomenon in the presence of other factors such as brand, price, safety level and maintenance costs. Conjoint methodology is employed to test the effect of COO in a multi-attribute model.